Motor lumbosacral radiculopathy in HIV-infected patients - Kaminie Moodley; Pierre L.A. Bill; Vinod B. Patel (AOSIS, 2019)
Background: This study is a review of the clinical findings and treatment outcome of 11 HIV-infected patients with motor lumbosacral radiculopathy. Objectives: To describe the clinical, laboratory, electrophysiological features and treatment outcome in HIV-infected motor lumbosacral radiculopathy which is a rare manifestation of HIV. Method: A retrospective review of HIV-infected patients with motor lumbosacral radiculopathy was performed at Inkosi Albert Luthuli Central Hospital (IALCH), Durban, South Africa between 2010 and 2015. Results: Eleven black African patients met the inclusion criteria. There were six women. The median age was 29 years, the interquartile range (IQR) was 23-41 years, the median duration of symptom progression was 6.5 months (IQR 3-7.5 months). The median CD4 count was 327 cells/µL (IQR 146-457). The cerebrospinal fluid (CSF) median polymorphocyte count was 0 cells/µL (IQR 0 cells/µL - 2 cells/µL), lymphocyte count was 16 cells/µL (IQR 1 cells/µL - 18 cells/µL), glucose level was 3.1 mmol/L (IQR 2.8 mmol/L - 3.4 mmol/L) and protein level was 1.02 g/dL (IQR 0.98 g/dL - 3.4 g/dL). All patients were treated with corticosteroid therapy. Ninety-one per cent recovered fully within 6 months of treatment, the median time for recovery was 3.4 months (IQR 1.8-5.6 months). There were no relapses during the 18-month follow-up. Conclusion: HIV-infected patients with motor lumbosacral radiculopathy responded to corticosteroids, with no relapses during the 18-month follow-up period.